Hukum Islam dan Budaya: Hubungan yang Kontras atau Komromi? - Muhammad Nasiuddin; Tutik Hamidah; Noer Yasin (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
The issue of Islamic law and culture is one of the central issues that generates different judgments in society. Some people think that Islamic law should be culturally sterile. while others believe that Islamic law can dialogue with culture with several aspects that must be considered to maintain the purity of Islamic law. This is closely related to the phenomenon where the model of understanding religious law and the religious behavior of adherents of religion (Islam) changes. This article attempts to consider the phenomenon of dialogue between religious law and culture in society and to describe the different characteristics of local Islamic law.